SurfChessVR: Deploying Chess Game on Parametric Surface in Virtual Reality - Li, Wanwan (International Conference on Virtual Rehabilitation (Print), 2023)
This paper proposes SurfChessVR, a novel gaming interface that deploys chess games on parametric surfaces in Virtual Reality (VR). Unlike traditional chess in VR where all chessmen are placed on a plane chessboard, our approach automatically places chessmen on arbitrary parametric surfaces such as spheres, torus, cones, etc. More specifically, given a mathematical equation that describes a parametric surface as input, our approach automatically generates the chessboard in the shape of that parametric surface and places the chessmen on that surface at different squares with corresponding orientations that align with the surface's normal directions. In order to deliver players with immersive gaming experiences of playing chess on a parametric surface, we implemented a game AI algorithm called the Min-Max algorithm that enables the computer to game against the player in VR. Experiment results and user studies validate the effectiveness and correctness of our approach.